Trend of Rainfall Pattern in Palembang for 20 Years and Link to El-niño Southern Oscillation (ENSO) - Ariska, Melly; Putriyani, Fena Siska; Akhsan, Hamdi; Supari, Supari; Irfan, Muhammad; Iskandar, Iskhaq (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
One factor that significantly affects rainfall in Indonesia, especially in Palembang City, is the El-Nino Southern Oscillation (ENSO). This study aims to determine how big the correlation is and when the highest correlation occurs between the Nino 3.4 Index and rainfall during the 2001-2020 period. The stages of analysis carried out to carry out this study are as follows: 1) downloading daily rainfall data for 20 years, 2) processing the raw data to make it homogeneous, and 3) correlation analysis to find out when the highest correlation occurs between rainfall and the Nino 3.4 Index. The results show that the highest correlation occurs in September at -0.524, August at -0.481, and October at -0.439. The influence of the Nino 3.4 Index produces a negative relationship. If the Nino 3.4 Index increases, it will affect the maximum temperature at the sea surface so that rainfall will decrease and cause drought. The results obtained can also be used as a prediction or forecast of the inflow of rainfall and the length of the rainy season.